Living Wages and Living Incomes in Fair Supply Chains? A Critical Review - Gröne, Katharina; Mayer, Isabell; Braun, Boris (DIE ERDE – Journal of the Geographical Society of Berlin, 2024)
The living wages and living incomes approach was designed to contribute to poverty reduction, environmental sustainability, and social justice. It is prominently positioned in the Fair Trade movement, which treats living wages and living incomes as a core political demand. While the concept of living wages and living incomes is not new, the challenges arising from a globalized, crisis-ridden world are increasingly complex and poorly understood. This special issue presents four international, wide-ranging empirical papers that, first and foremost, ask whether living wages and living incomes provide socially just and sustainable livelihoods for workers and smallholder farmers in countries that produce key primary commodities, mainly in the Global South. This editorial first reviews the origins and evolution of the living wages and living incomes concept and different methods of calculation. It then previews the empirical contributions in this special issue and discusses the practical implementation challenges of living wages and living income ideals.